Learning to Theorize in a Complex and Changing World - Hillary Swanson; Allan Collins (Foresight and STI Governance)
To thrive in the modern world, people need to make sense of complex issues and deal with uncertainty. This requires a different kind of knowledge than schools are teaching. We argue that cultivating a theoretical turn-of-mind is critical for identifying causal relationships and patterns within any phenomenon and trend. In this paper, we introduce a course designed to engage students in an “intellectually honest” version of scientific theory building. We describe four theory-building competencies that students developed as a result of their participation in the course and highlight the features of instruction that may have played a key role in this development. We describe how a particular feature of the course - the theory-building discussion - helped students refine their thinking and we outline the moves the teacher used to facilitate the refinement process. We conclude that learning to construct theories is beneficial even for students who are not tending towards careers in science, as it helps to refine everyday thinking, and, in a broader sense, build human capacities to develop solutions for the complex problems we face across economics, environment, health, and many other domains.